Structural and Functional Changes Are Related to Cognitive Status in Wilson’s Disease - Hu, Sheng; Xu, Chunsheng; Dong, Ting; Wu, Hongli; Wang, Yi; Wang, Anqin; Kan, Hongxing; Li, Chuanfu (Frontiers in Human Neuroscience, 2021)
Patients with Wilson’s disease (WD) suffer from prospective memory (PM) impairment, and some of patients would develop into cognitive impairment. However, very little is known about how brain structure and function changes have effect on PM in WD. Here, we employed multimodal neuroimaging data acquired from 22 WD patients and 26 healthy controls who underwent three-dimensional T1-weighted, diffusion tensor (DTI), and resting state functional magnetic resonance imaging (RS-fMRI). We investigated gray matters (GM) volumes with voxel-based morphometry, DTI metrics using fiber tractography method, and RS-fMRI using seed-based functional connectivity method. Compared with healthy controls, WD patients showed GM volumes reduction in the basal ganglia and Occipital fusiform gyrus, as well as volumes increasing in visual association cortex. Moreover, whiter matter (WM) tracks of WD were widely impaired in association and limbic fibers. WM tracks in association fibers are significant related to PM in WD patients. Relative to healthy controls, WD patients showed that visual association cortex functionally aberrant connects to thalamus and hippocampus, which is associated with global cognitive function in patients with WD. Together, These findings suggested that PM impairment in WD may modulate by aberrant WM in association fibers, and that GM volume changes in association cortex has no direct effect on cognitive status, but indirectly affect global cognitive function by its aberrant functional connectivity in patients with WD. Our findings may provide a new window to further study how WD develop into cognitive impairment, and deepen our understanding of cognitive status and neuropathology of WD.